Programming PHP - Lerdorf, Rasmus, ....-; Kaehms, Bob, ....-; Tatroe, Kevin, ....- (Sebastopol (Calif.) : O'Reilly, 2002)
Samenvatting:Now, more than ever, the Web is a major vehicle for corporate andpersonal communications. Web sites carry photo albums, shopping carts,and product lists. Many of those web sites are driven by PHP, an opensource scripting language primarily designed for generating HTML content.Since its inception in 1994, PHP has swept over the Web. The millions ofweb sites powered by PHP are testament to its popularity and ease of use.It lies in the sweet spot between Perl/CGI, Active Server Pages (ASP),and HTML. Everyday people can learn PHP and can build powerful dynamicweb sites with it.The core PHP language features powerful string- and array-handlingfacilities, as well as support for object-oriented programming. With theuse of standard and optional extension modules, a PHP application caninteract with a database such as MySQL or Oracle, draw graphs, create PDFfiles, and parse XML files. You can write your own PHP extension modulesin C-for example, to provide a PHP interface to the functions in anexisting code library. You can even run PHP on Windows, which lets youcontrol other Windows applications such as Word and Excel with COM, orinteract with databases using ODBC.This book is a guide to the PHP language. When you finish this book, youwill know how the PHP language works, how to use the many powerfulextensions that come standard with PHP, and how to design and build yourown PHP web applications.
Keywords: Informatiesystemen; Internet; PHP (=programmeertaal).; PHP (Computer program language).; Programmeertaal; Web sites -- Design; Webdesign